Diffuse leptomeningeal glioneuronal tumor with atypical radiological and molecular feature: A case report and literature review - Lingxu Chen; Junmei Wang; Xiaochen Wang; Sihui Wang; Xuening Zhao; Shengjun Sun (Interdisciplinary Neurosurgery, 2024)
A Diffuse Leptomeningeal Glioneuronal Tumor (DLGNT), a rare entity as classified in the World Health Organization’s Fifth Edition of the Classification of Tumors of the Central Nervous System (WHO CNS5), is characterized by oligodendrocyte-like cells with MAPK pathway alterations. This report details the case of a 29-year-old female presenting with unique radiological features: extensive spinal cord dissemination involving both parenchyma and leptomeninges, without intracranial involvement. Near-total resection (NTR) was performed, revealing H3K27me3 positivity, a molecular characteristic not previously reported in DLGNTs. We also review recent studies to expand the understanding of DLGNT’s clinical, imaging, and molecular profiles, aiming to assist radiologists and clinicians in accurate diagnosis and timely management.